The Influence of Motivation and Leadership on Employee Performance Through Job Satisfaction in the Secretariative Bureau Leader of the Secretariat of the House of Representative of the Republic of Indonesia - Kaelani, Muhammad Rodli; Wibowo, Imam; Harry Indratjahyo (Krisnadwipayana International Journal of Management Studies, 2023)
Job satisfaction is something that will support or not support an employee in relation to their work or their condition. Considering that the House of Representative of the Republic of Indonesia’s (DPR RI) Leadership Secretariat Bureau is one of the spearheads which is directly related to optimizing the work of the DPR RI Leadership which is a reflection of the DPR RI institution, it is appropriate for employees within the DPR RI Leadership Secretariat Bureau to provide and demonstrate good and capable performance. Based on this, the author wants to research more deeply into the influence of motivation and leadership on employee performance through job satisfaction. This research is field research conducted at the Secretariat Bureau of the House of Representative of Indonesia. The population of this research is the State Civil Apparatus within the Secretariat Bureau of the Secretariat General of the DPR RI. Meanwhile, the sample used was all 70 employees through distributing questionnaires. The data analysis method uses the Path Analysis model to analyze the relationship patterns between variables with the aim of determining the direct and indirect influence on the independent (exogenous) and dependent (endogenous) variables. The research results show that work motivation and leadership have a positive and significant effect on employee performance. Work motivation and leadership have a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Work motivation and leadership do not have a positive and significant effect on employee performance through job satisfaction in the Secretariat Bureau for the Leadership of the Secretariat General of the DPR RI.